2001
DOI: 10.1067/mtc.2001.116316
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent arch obstruction after repair of isolated coarctation of the aorta in neonates and young infants: Is low weight a risk factor?

Abstract: Low weight is not a risk factor for recurrent obstruction after repair of coarctation of the aorta in infants less than 3 months of age. Rather, risk of recoarctation is more a function of the anatomy of the arch. Thus, it is not indicated to delay repair in low weight infants with the goal of achieving growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
74
5
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(87 citation statements)
references
References 16 publications
6
74
5
2
Order By: Relevance
“…Serial studies may be indicated at routine intervals for monitoring of valve function, growth of cardiovascular structures, ventricular function, and potential sequelae of medical or surgical intervention. [15][16][17][18] Congenital Heart Disease: History, Symptoms, and Signs…”
Section: Indicationsmentioning
confidence: 99%
“…Serial studies may be indicated at routine intervals for monitoring of valve function, growth of cardiovascular structures, ventricular function, and potential sequelae of medical or surgical intervention. [15][16][17][18] Congenital Heart Disease: History, Symptoms, and Signs…”
Section: Indicationsmentioning
confidence: 99%
“…1 With this important caveat, reintervention after surgical repair of CoA appears to vary widely, depending on subject size, anatomy, era, and technique of repair. [12][13][14][15][16][17][18][19] Except in unusual situations, there are no planned surgical reinterventions. In contrast, planned reintervention on endovascular stents, either as a part of a staged approach to severe arch obstruction or as a part of stent therapy in growing patients, is well documented.…”
Section: Clinical and Hemodynamic Outcomes And Reintervention Ratesmentioning
confidence: 99%
“…1,2,4,5 The majority of recoarctation occurs within the first postoperative year 1,5,6 and even in the absence of recoarctation, up to 30% of children develop significant systolic arterial hypertension despite early repair. 18 -20 Arterial physiology studies have shown significant abnormalities in young adults postcoarctation repair.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,4,5 However, recurrent stenosis can occur leading to further invasive procedures. 1,2,5,6 The surgical procedure, itself, may contribute to this complication. It requires resection of all ductal tissue, and in case of arch hypoplasia, greater extension of the anastomosis, thus increasing the distance between the severed aortic ends.…”
mentioning
confidence: 99%